JUVENILE DELINQUENCY IN JAY ASHER’S NOVEL THIRTEEN REASONS WHY - Alda Dwi Afangka; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2021)
This study is aimed at analyzing juvenile delinquency in Jay Asher’s novel, Thirteen Reasons Why, published in 2007. Further, the analysis is focused on the forms of juvenile delinquency covering bullying, drinking alcohol, having free sex, and having sexual harrasment done by the characters of the novel named Hannah Baker, Bryce Walker, Justin Foley, Alex Standall, Jessica Davis, Courtney Crimsen, Marcus Cooley, and Bryce Walker. This research is conducted to reveal the forms of juvenile delinquency conducted by the main characters in the novel. This study is qualitatively carried out. In this study, the researchers apply the theory of juvenile delinquency proposed by Santrock, supported by that proposed by Kartono referring to a variety of behavior of children and adolescents which the society does not approve and for which some kind of admonishment, punishment, or preventive and corrective measures are justified in the public interest. The research results show that the forms of juvenile delinquency: bullying, drinking alcohol, having free sex, and having sexual harassment are vividly reflected and clearly done by the main characters in the novel.